IDENTITY AND HERITAGE IN GARCIA’S OF WOMEN AND SALT:A DIASPORIC STUDY (Contemporary Journal of Social Science Review, 2025)
This paper examines the entanglements of identity and heritage in Gabriela Garcia’s Of Women and Salt (2021), and interrogates the ways in which these ideas are formed, inherited and contested in diaspora. In a critical diasporic light, the novel presents the impact of displacement, migration, memory and intergenerational trauma on the lives of Latina women moving through cultural dislocation and political conflict. This study investigates how the novel projects mother-daughter relationships, language, memory and exile as key components of diasporic identity. The paper also demonstrates that Garcia places heritage not as static inheritance but as ongoing process. Frequently, this is painful process of recollection and reinterpretation. This research portrays characters’ struggle to define home especially when home is a moving entity. By putting female voices at its centre, Of Women and Salt disrupts white supremacist history in order to record the endurance of people in the face of loss and violence. It also creates the possibility of people to reinvent themselves and their world. Conclusively, this project contends that Garcia’s novel provides a sophisticated consideration of how diasporic subjects make sense of self through ruptures and continuities. Besides, where one’s background is both wound and salve, and identity is formed and reformed by the push and pull between remembering and forgetting history.